KERAGAMAN BAKTERI PENAMBAT N PADA RHIZOSFIR TITONIA (Tithonia diversifolia) YANG TUMBUH PADA TANAH MASAM ULTISOL - Agustian Agustian; Rimadhani Syafei; Lusi Maira (Jurnal Solum, 2012)
Research on biodiversity of  N-fix bacteria was performed on rhizosphere  of Tithonia diversifolia grown at acid soil Ultisol. This study aimed to determine the biodiversity and populations of N-fix bacteria along with the growth rate of Tithonia and characterized the bacterial isolates obtained from the rhizosphere of this plant. Soil rhizosphere samples were taken from rhizospheres of Tithonia with different criteria of stem diameter i.e Ø <3 cm, and 3 to 6 cm that grown  at Faculty of Agriculture Andalas University experimental station.From these results it can be concluded that the diverse and larger population were  found in Tithonia with 3 to 6 cm stem diameter  an average of 19.7 x 103 cfu per g of soil. N-fix bacterial isolates obtained have a round, slimy, slippery and convex colonies and gram variable. Based on the color of their colonies, N-fix bacterial isolates obtained were classified into 3 groups with the following characteristics: (1) white milk isolates (A1ps, a2ps, B3ps), flourescent white and yellow, have flagella and produce auxin, (2) yellow isolate (B2K and B3K), with yellow flourescent, have flagella and produce auxin, and (3) the clear isolates that could separated into two groups i.e the flourescent group and produce auxin and has flagella isolates (A2b, A3b, and B2b) and non flourescent group, no flagella and does not produce auxin isolates (B1b, B3B). The optimum growth conditions for the all isolates were pH media nearly 7 with 35o C incubation temperature. The translucent isolates (A3b and B3B) have a optimum range pH from 4.36 to 6.17, while isolates with a yellow colonies (B2K) has a range of incubation temperature 25oC to 35oC. However, from the characterization performed could not permit to specify the isolates obtained into species.Key words : Biodiversity, N-fix bacteria, rhizosphere, Tithonia diversifolia